Income Inequality in a Democratic and Social Perspective in Indonesia - Candra Mustika; Haryadi Haryadi; Junaidi Junaidi; Zamzami Zamzami (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
The purpose of this study was to determine and analyze the influence of the democracy index, aspects of civil liberties, aspects of political rights, and aspects of democratic institutions, crime rates, access to information from the internet, on inequality in income distribution. The research method used in this study is descriptive quantitative using panel data multiple regression analysis. This study uses panel data with objects from 34 provinces in Indonesia with a research period from 2014 to 2020. Based on the results of panel data regression with a random effects model, it shows that aspects of democracy both in general through the democracy index variable and specifically through the variable aspects of civil liberties, aspects of political rights and aspects of democratic institutions both have a positive and significant effect on income distribution inequality, as well as the variable number of criminal acts has a significant positive effect on income distribution inequality. Meanwhile, access to information has a significant negative effect on income distribution inequality.quality.